2020
DOI: 10.1590/0103-8478cr20190447
|View full text |Cite
|
Sign up to set email alerts
|

Testers in supersweet corn lines

Abstract: The purpose of this study was to evaluate the discriminatory capacity of tester lines for tropical corn lines converted to supersweet shrunken (sh2) gene, for the development of hybrids adapted to tropical conditions. Lines were used as female parents in crosses with three testers: open-pollinated mixed variety; supersweet line L4; supersweet commercial hybrid Tropical Plus. Four trials were carried out to evaluate topcrosses in Maringá - PR e Sabáudia - PR, Brazil in the main growing season of 2015/16. The fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In a similar study, Ref. [73] observed that the crosses BALU-182 × Tropical and BALU-94 × Mista exceeded their parents in cob and grain weight, so the specificity between the parents involved in the crosses was exhibited, Seeds 2024, 3 164 which was explained by the effects of GCA and SCA, where the effects of the GCA were higher than those of the SCA for all the traits, indicating that the additive effects are more important than the dominant ones [11] and where the GCA explained the best parent and the SCA explained the most promising crosses.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In a similar study, Ref. [73] observed that the crosses BALU-182 × Tropical and BALU-94 × Mista exceeded their parents in cob and grain weight, so the specificity between the parents involved in the crosses was exhibited, Seeds 2024, 3 164 which was explained by the effects of GCA and SCA, where the effects of the GCA were higher than those of the SCA for all the traits, indicating that the additive effects are more important than the dominant ones [11] and where the GCA explained the best parent and the SCA explained the most promising crosses.…”
Section: Discussionmentioning
confidence: 78%
“…It is seen that a viable option for High Valleys in Mexico could be the use of crosses between genotypes or races with traits that prosper under conditions of water stress and from deep sowing, such as the LM-LC. This could be a selection criterion to improve genotypes that are less outstanding in the regions of High Valleys in Mexico, where it has been observed that the races Cacahuacintle, Cónico and Chalqueño show specific traits that allow them to develop [47] at altitudes of 2200 to 3000 m, where corn sowing prevails under conditions of "irrigation tip", residual humidity and rainfed with low temperature events (frosts) [73] and where seeds must frequently be deposited at around 20 to 30 cm deep to reach the moisture available. Therefore, they could be useful populations in later studies related to stress from deep sowing, such as crosses 1 × 2, 1 × 3 and 2 × 3 from parent combinations (H-48, HS-2 and Promesa) of long mesocotyls, which presented favorable associations based on the PCA (Figures 6 and 7).…”
Section: Discussionmentioning
confidence: 99%